Analysis of proteins and peptides by electromigration methods in microchips - Štěpánová, Sille; Kašička, Václav (Journal of separation science, 2017)
This review presents the developments and applications of microchip electromigration methods in the separation and analysis of peptides and proteins in the period 2011-mid-2016. The developments in sample preparation and preconcentration, microchannel material, and surface treatment are described. Separations by various microchip electromigration methods (zone electrophoresis in free and sieving media, affinity electrophoresis, isotachophoresis, isoelectric focusing, electrokinetic chromatography, and electrochromatography) are demonstrated. Advances in detection methods are reported and novel applications in the areas of proteomics and peptidomics, quality control of peptide and protein pharmaceuticals, analysis of proteins and peptides in biomatrices, and determination of physicochemical parameters are shown.
Keywords: elektrochemické techniky; Electrochemical Techniques; Isoelectric Focusing; Microchip Analytical Procedures; isoelektrická fokusace; Microchip electrophoresis; mikročipové analytické postupy; Proteomics; Microfluidics; peptidy; proteiny; proteomika; Peptides; Proteins